Home gardens in the Paschim Medinipur District of West Bengal in India: a land use system with multiple benefits. (1st January 2015) - Jana, Sebak; Roy, Joyashree; Marambe, Buddhi; Weerahewa, Jeevika; Pushpakumara, Gamini; Silva, Pradeepa; Miah, Md. Giashuddin; Punyawardena, Ranjith; Premalal, Sarath
'Home garden' (HG) is a complex sustainable land use system combining annual and perennial crops, trees, shrubs, livestock and fishery. The flow of goods and services provides not only food and nutrition security and employment, but also other co–benefits. Though HGs have attracted international attention since 1950s, it has not been widely researched especially in the context of rural India. This paper presents the results based on a field study carried out in 100 HGs in Paschim Medinipur District in the West Bengal, located in eastern part of India. A structured questionnaire was used to identify different aspects related to HG characteristics, their role in household consumption, problem areas and the different socio–economic characteristics of the HG owners. The results suggest that home gardeners with a higher level of education and who are using modern inputs are able to derive more benefits from the HGs.